THE EFFECT OF PAYMENTS FOR THE STATE DEBT ON FORECAST INDICATORS OF THE BUDGET SECURITY OF THE STATE - Posadnieva, O. M.; Berezynska , M. O. (The actual problems of regional economy development, 2024)
The article examines the problem of the accumulation of the national debt of Ukraine, indicates the reasons for its growth, emphasizes the worsening of the debt situation in connection with military operations on the territory of the country. When writing the article, the methods of analysis and synthesis, the method of generalizations and statistical methods were used. The paper examines the main factors that caused the debt to grow. The impact of public debt servicing costs on the indicators of the State Budget of Ukraine is analyzed. The unevenness of expenditures from the state budget for the repayment and servicing of the state debt over the past ten years was emphasized. To assess the level of budgetary security of the state in the future, forecast data on the growth of the main macroeconomic indicators for the next three years are given. The GDP growth forecast for the next three years, forecast indicators of state budget revenues are highlighted. The elasticity coefficient was used to calculate the forecast values ​​of revenues of the Consolidated Budget of Ukraine. The real and forecast ratio of the volume of aggregate payments for servicing and repayment of the state debt and revenues of the State Budget of Ukraine is shown. The possibilities of reducing the budget deficit at the current stage of development of the domestic economy have been assessed. Four main indicators of the state's budgetary security are described. An analysis of indicators of Ukraine's budgetary security over the past ten years was carried out. The sharp deterioration of budgetary security indicators in 2022 and 2023 due to the war on the territory of Ukraine is emphasized. Emphasis is placed on the indicator of the ratio of the volume of aggregate payments for servicing and repayment of the state debt to the revenues of the state budget as the one that had the worst indicators for the entire period under study. A forecast of indicators of the state's budgetary security for the next three years has been made. The main trends for each of the indicators were analyzed. The work noted that most indicators of budgetary security have positive trends of change in the medium term. It was emphasized that the forecast for 2024 has the worst indicators of budget security due to the significant volume of planned payments on the public debt. Conclusions were made regarding the prospects of Ukraine's budget security. Recommendations are provided for the conduct of debt policy in the future.